Causes of Scholastic Dishonesty among the Examinees - Rai, Ravi Prakash (JOURNAL OF INDIAN EDUCATION, 2013)
The present study was an attempt to explore the causes of scholastic dishonesty among the examinees. Random sampling procedure was used to select 100 teachers and 300 students of graduate class. A self-constructed checklist was administered to collect the data. Simple percentage and ranks were calculated. The obtained results indicate that teachers and students differ with regard to the causes of scholastic dishonesty among the examinees.